KEANEKARAGAMAN ARTHROPODA PERMUKAAN TANAH PADA TANAMAN CABAI (Capsicum annum L.) DENGAN SISTEM PERTANAMAN YANG BERBEDA DI KABUPATEN SIGI - Moh. Hibban Toana, Abd. Wahid, Agustinawati (AGROTEKBIS, 2016)
This research objective was to determine the diversity of Arthropods on the soil surface of Chili (Capsicum annum L.) cropping with different systems in Sigi district. The research conducted from January to April 2015, at Jono Oge village, Sigi Biromaru Sub district, Sigi District and Sunju village, Marawola Sub district, Sigi District. Insect identification was carried out in the Plant Pests and Diseases Laboratory, Agriculture Faculty, Tadulako University, Palu. The research site was determined intentionally (purposive sampling) inÂ  a number of farmersâ Chili cropping where each cropping covering an area of 12 x30 m2.Â  The arthropod samples were taken using a pitfall trap with a row method. The arthropod observations were performed 8 times starting when the plant aged three weeks. The observations showed the number of insects (2067) on the intercropping at Jono Oge villageÂ  is higher than those insects (1451) on theÂ  monoculture at Sunju village. The soil surface arthropods obtainedÂ  in Jono Oge village were 21 species and in Sunju village were 17 species. Based on the analysis of diversity index (H), Sunju village HÂ  is higher than Jono Oge village, but the diversity index of both villages is categorized sufficient.